Carefree conferences? Academics with caring responsibilities performing mobile academic subjectivities. Issue 1 (2nd January 2020) - Henderson, Emily F.; Moreau, Marie-Pierre
ABSTRACT: This article explores how academics with caring responsibilities negotiate the mobility imperative, with specific reference to attending conferences. We argue that, in the neoliberal and 'careless' context of higher education, negotiating conflicting identities of academic and carer are fraught with tensions for carers as they try to reconcile the mobility imperative with their caring responsibilities. We acknowledge and also challenge the naturalised relationship between care and femininity, and use a feminist poststructuralist approach to analyse the competing discourses surrounding academic and care work. We draw on two distinct, but related, research projects with predominantly UK-based participants. Moreau's project ('Carers and Careers', 2015–2017) explored how academic carers negotiate academic cultures which tend to render care work invisible, using interviews with academic carers and policy staff. Henderson's project ('In Two Places at Once', 2017–2018) focused on the impact of caring responsibilities on academics' conference participation, using diary-interview method.